An Investigation of Self-Directed Learning Skills of Undergraduate Students - Tekkol, İlkay Aşkin; Demirel, Melek (Frontiers in Psychology, 2018)
The aim of this study is to reveal university students’ self-directed learning skills and determine whether these skills vary based on university type, gender, field of study, year of study, academic success, type of university entrance score, income level, and the will to pursue a graduate degree. Also, the study also explored the relationship between university students’ self-directed learning skills and their lifelong learning tendencies. The study group of the survey comprised 2,600 first and fourth-year students from similar departments of Hacettepe and Başkent Universities. The study collected its data with the “Self-Directed Learning Skills Scale” designed by Aşkın (2015). Moreover, Diker-Coşkun’s “Lifelong Learning Tendencies Scale” was used to explore the relationship between university students’ self-directed learning skills and their lifelong learning tendencies. The results showed that university students’ self-directed learning scores were above the median score of the scale. Self-directed learning skills were found not to vary based on university, year of study, income level. However, gender, field of study, university entrance score type, academic success and the will to pursue a graduate degree made a significant difference on university students’ self-directed learning skills. Finally, a moderate positive relationship was detected between self-directed learning skills and lifelong learning tendencies.